c.7156C > T p.(Gln2386*) variant causes loss-of-function of the USP9X gene in a female-restricted X-linked syndromic intellectual disability: a case report - Talyta Alves da Silva Campos; Alex Honda Bernardes; Irene Plaza Pinto; Hiane Aparecida da Silva Teixeira; Juliana Ferreira da Silva; Victor Cortázio do Prado Santos; Raffael Zatarin; Aparecido Divino da Cruz (Journal of Medical Case Reports)
Abstract Background Female-restricted X-linked syndromic intellectual developmental disorder-99 is an ultrarare neurodevelopmental disorder linked to X, manifesting in female individuals due to mutations in the USP9X gene. It is characterized by developmental delays, behavioral alterations, and moderate-to-severe intellectual disability. The USP9X gene plays critical roles in protein turnover and the regulation of essential pathways during neural development. This work describes the case of a Brazilian patient with female-restricted X-linked syndromic intellectual developmental disorder-99 with a variant not found in databases such as Decipher and ClinVar. Information was obtained from the Center for Rehabilitation and Readaptation Dr. Henrique Santillo electronic medical record system, and exams were conducted by partner laboratories of the Unified Health System. Documenting cases in different populations enriches the knowledge of genetic variations, guides personalized treatments, and expands the field of medical genetics, underscoring the importance of this study. Case presentation A 3-year-old female patient of Pardo admixed ethnicity from northern Brazil was referred to the Center for Rehabilitation and Readaptation Dr. Henrique Santillo for suspected genetic disorders. The child was born after an uneventful pregnancy but faced neonatal complications, including cardiopulmonary arrest and jaundice, requiring intensive care unit admission. She was diagnosed with nonprogressive encephalopathy and neuropsychomotor developmental delay. Additional tests revealed structural anomalies, such as corpus callosum agenesis and congenital hip dysplasia. Various genetic tests were performed, but only whole exome sequencing revealed a pathogenic variant in the USP9X gene, associated with female-restricted X-linked syndromic intellectual developmental disorder-99. Conclusion We report the case of a child with a heterozygous pathogenic variant in the USP9X gene, located at Xp11.4 and presenting a wide range of phenotypes. The cytosine-to-thymine substitution resulted in a premature stop codon, causing female-restricted X-linked syndromic intellectual developmental disorder-99. The mutation leads to protein function loss due to haploinsufficiency, resulting in a dominant X-linked disorder. Loss-of-function mutations in the USP9X gene cause intellectual disability and congenital anomalies, with several craniofacial anomalies observed in the patient. Despite the de novo nature of most loss-of-function variants, maternal testing is crucial for estimating recurrence risk. Genetic investigation confirmed the variant’s pathogenicity, highlighting diagnostic challenges and the importance of genetic research in understanding and managing female-restricted X-linked syndromic intellectual developmental disorder-99. Graphical Abstract